Ivanovskai︠a︡ guba / Sostavleno v 1902 g. po robotam Gidrograficheskoĭ ėkspedit︠s︡ii Severnogo Ledovitogo okeana v 1901 g. - Soviet Union. Gidrograficheskoe upravlenie; (Leningrad : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Ленинград] : Морское министерство, Главное гидрографическое управление СССР, 1926)
Mal. korrekt. X-1920 Bolʹsh. korrekt. X-1925; Мал. коррект. X-1920 Больш. коррект. X-1925.; Relief shown by form lines. Depths shown by soundings.; Main title translation: Ivanovsky Bay.; Top margin title translation: Arctic Ocean, Murmansk coast.; Includes two tables and note.; Greenwich meridian.; Coordinates given for Ivanovskaya Bay (Guba Ivanovskaya) on map: 68°19'51.8"N 38°30'00.0"E.; "Masshtab 1/16800 ili 200 sazh. 7-ti fut. mery v di︠u︡ĭme = Scale 1/72000 or 200 7-foot fathoms in 1 inch.; "Sostavleno v 1902 g. po robotam Gidrograficheskoĭ ėkspedit︠s︡ii Severnogo Ledovitogo okeana v 1901 g. = Compiled in 1902 according to the work of the Hydrographic Expedition of the Arctic Ocean of 1901.; "No. 586" -- margins Color; 1:16,800